The “Mundialito shipibo”: identity, ethnicity and modernity in the Peruvian Amazon - Espinosa, Oscar (2020)
For nearly thirty years, the Mundialito shipibo, a football (soccer) championship has been held in the city of Pucallpa, in the Peruvian Amazon region, bringing together Shipibo-Konibo families from the different communities located along the Ucayali river, but also from other parts of the country as well. Through time, the Mundialito has undergone important changes, trying to become more modern and professional. However, at the same time, the Mundialito can be seen as a new version of the traditional ani xeati, the big feast of the Shipibo people. Therefore, nowadays, the Mundialito is not only a sports event, but also a moment in which relatives get together, indigenous leaders meet, young people get to know each other and form new couples, commercial exchanges are made, and, of course, as in any other big celebration, people eat and drink together, dance and celebrate together.